Visual elements and cognitive development in early education: a content analysis of nature-themed picture books in China - Sun, Chao; Hussain, Norhuzailin; Abd Ghafar, Azmiah; Noordin, Nooreen (Springer Science and Business Media B.V., 2026)
Nature-themed picture books are increasingly used as vital media within early education settings to support children’s understanding of nature and environmental issues. However, within the Chinese context, systematic discussions regarding their visual representation remain relatively limited. This study aims to identify the distribution of natural sub-themes, age labels, and visual elements in nature-themed picture books published in China, and to compare variations in visual representation across sub-themes and age label groups. This study employs content analysis to examine 47 award-winning nature-themed picture books published between 2015 and 2023. Each book is analysed at the book level and, according to a coding scheme, assigned one sub-theme and one age label, as well as three visual elements, including image form, image style, and colour scheme. Results indicate that the sample predominantly features realistic, full-colour illustrations as the mainstream visual representation, emphasising clear cues and stable referents. Furthermore, current natural content remains predominantly focused on fundamental natural laws and biological knowledge, with relatively limited coverage of complex issues such as pollution. Visual differentiation between sub-themes is insufficient, and there is a degree of cognitive misalignment between age labels and visual representation. This study provides empirically testable evidence for optimising nature-themed picture books in terms of theme, age labels, and visual representation, suggesting that future work should enhance thematic differentiation and more explicitly align with the cognitive characteristics of different age groups.